2019
DOI: 10.1038/s41598-019-46047-5
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic pollutant-driven geographical distribution of mesozooplankton communities in estuarine areas of the Bohai Sea, China

Abstract: Mesozooplankton communities in marine ecosystems are mainly influenced by both anthropogenic pollutants (e.g. nutrients and heavy metals) and natural variables (e.g. temperature, salinity and geographic distance). To achieve a deeper understanding of the effects of anthropogenic pollutants on mesozooplankton communities, we analyzed the community structure of mesozooplankton from 91 stations representing five typical estuarine regions in the Bohai Sea and assessed the relative importance of anthropogenic pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…In recent decades, serious environmental pollution has resulted from the rapid economic and industrial development of China’s coastal areas. A large amount of trace metals such as cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), and zinc (Zn) are released into the marine environment, all of which bioaccumulate in seafood and pose a serious human health risk (Li et al 2018 ; Zhang et al 2016 ; Gao et al 2019 ). Liaodong Bay is a semi-enclosed water body located in the northern region of the Bohai Sea, which is impacted by trace metal pollution derived from several industrial and agricultural activities along its coast.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, serious environmental pollution has resulted from the rapid economic and industrial development of China’s coastal areas. A large amount of trace metals such as cadmium (Cd), chromium (Cr), copper (Cu), lead (Pb), and zinc (Zn) are released into the marine environment, all of which bioaccumulate in seafood and pose a serious human health risk (Li et al 2018 ; Zhang et al 2016 ; Gao et al 2019 ). Liaodong Bay is a semi-enclosed water body located in the northern region of the Bohai Sea, which is impacted by trace metal pollution derived from several industrial and agricultural activities along its coast.…”
Section: Introductionmentioning
confidence: 99%
“…Estuaries are transitional zones between rivers and oceans and are characterized by complex hydrodynamics and chemical conditions (Van der Linden et al, 2017); they are also some of the most anthropogenically disturbed aquatic systems and are sensitive to environmental changes (Wetzel et al, 2012;Gao et al, 2019;Hillman et al, 2020). High variability in this physicochemical has a substantial effect on biological communities, and only a few highly dominant species are capable of thriving in such environments (Elliott and Quintino 2007).…”
Section: Es Of the Benthic Ecosystem And Its Relationship With Environmental Factorsmentioning
confidence: 99%
“…With their complex hydrodynamics, estuaries have been important areas for human settlement, and they also represent some of the most productive natural ecosystems on Earth (Costanza et al, 1997;Lotze et al, 2006;van der Linden et al, 2012). Their health is key to the development of human society, but anthropogenic and natural stressors have increased estuarine ecosystem deterioration and biodiversity loss (Barbier et al, 2011;Gao et al, 2019;Hillman et al, 2020;Spreitzenbarth and Jeffs, 2021). For example, many anthropogenic pollutants such as dissolved inorganic nitrogen (DIN) can lead to eutrophication, which decrease the survival of sensitive species, reduces species diversity, and simplifies food webs (Alexander et al, 2017;Gao et al, 2019;Ji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bohai Sea is located in Northeast China and has been influenced by anthropogenic factors in recent years [23,24]. Previous studies revealed that the pollution in Bohai Sea is serious in coastal areas and that situation can be worse if no protection procedures are implemented [25].…”
Section: Introductionmentioning
confidence: 99%